Genome-wide identification and characterization of tissue specific long non-coding RNAs and circular RNAs in common carp (Cyprinus carpio L.) - Das, Jutan; Kumar, Baibhav; Saha, Bibek; Jaiswal, Sarika; Iquebal, Mir Asif; Angadi, U. B.; Kumar, Dinesh (Frontiers in Genetics, 2023)
Cyprinus carpio is regarded as a substitute vertebrate fish model for zebrafish. A varied category of non-coding RNAs is comprised of long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs). These ncRNAs were once considered non-functional “junk DNA” but research now shows they play important roles in gene expression regulation, chromatin modification, and epigenetic regulation. The systemic tissue-specific research of the lncRNAs and circRNAs of C. carpio is yet unexplored. A total of 468 raw RNA-Seq dataset across 28 distinct tissues from different varieties of common carp retrieved from public domain were pre-processing, mapped and assembled for lncRNA identification/ classification using various bioinformatics tools. A total of 33,990 lncRNAs were identified along with revelation of 9 miRNAs having 19 unique lncRNAs acting as their precursors. Additionally, 2,837 miRNAs were found to target 4,782 distinct lncRNAs in the lncRNA-miRNA-mRNA interaction network analysis, which resulted in the involvement of 3,718 mRNAs in common carp. A total of 22,854 circRNAs were identified tissue-wise across all the 28 tissues. Moreover, the examination of the circRNA-miRNA-mRNA interaction network revealed that 15,731 circRNAs were targeted by 5,906 distinct miRNAs, which in turn targeted 4,524 mRNAs in common carp. Significant signaling pathways like necroptosis, NOD-like receptor signaling pathway, hypertrophic cardiomyopathy, small cell lung cancer, MAPK signaling pathway, etc. were identified using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes. The web resource of common carp ncRNAs, named CCncRNAdb and available at http://backlin.cabgrid.res.in/ccncrnadb/ gives a comprehensive information about common carp lncRNAs, circRNAs, and ceRNAs interactions, which can aid in investigating their functional roles for its management.